2018
DOI: 10.1038/s41598-018-22318-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming in Amyotrophic Lateral Sclerosis

Abstract: Mitochondrial dysfunction in the spinal cord is a hallmark of amyotrophic lateral sclerosis (ALS), but the neurometabolic alterations during early stages of the disease remain unknown. Here, we investigated the bioenergetic and proteomic changes in ALS mouse motor neurons and patients’ skin fibroblasts. We first observed that SODG93A mice presymptomatic motor neurons display alterations in the coupling efficiency of oxidative phosphorylation, along with fragmentation of the mitochondrial network. The proteome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 63 publications
7
52
0
Order By: Relevance
“…In our studies, fibroblasts are grown in medium with a high glucose level, meaning that the high respiration rate observed in fALS cells might be explained by disturbances in glycolysis. It was shown that components of the glycolysis pathway were lower in ALS patients' skin fibroblasts than in controls (69). The high respiration rate in fALS fibroblasts might also be a compensation effect in response to their low DC m .…”
Section: Discussionmentioning
confidence: 95%
“…In our studies, fibroblasts are grown in medium with a high glucose level, meaning that the high respiration rate observed in fALS cells might be explained by disturbances in glycolysis. It was shown that components of the glycolysis pathway were lower in ALS patients' skin fibroblasts than in controls (69). The high respiration rate in fALS fibroblasts might also be a compensation effect in response to their low DC m .…”
Section: Discussionmentioning
confidence: 95%
“…Unlike other studies of the whole plasma proteome in ALS, here we show that the protein composition of plasma CPA from ALS individuals reproduces most of the extensively described pathological hallmarks of ALS, including pathways involved in protein degradation through the proteasome and energy metabolism ( 52-55 ). The same approach applied to the TMT-proteomic datasets reveals regulated features also known to be involved in ALS pathology and in protein aggregates homeostasis including lysosome as well as lipoprotein and glycosaminoglycan metabolisms ( 33,34,45,48,49,(52)(53)(54)(55) ) (Table S4). All disease-related alterations in proteasome activity in ALS have so far been shown in such detail only in brain, spinal cord and in neuronal cell lines, but not systemically or more specifically in blood, as in our study ( 52,53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within the top ten regulated pathways, five were involved in metabolism of lipoproteins (Table S4). The significant representation of these pathways in our brain/CPA proteomes reflects known changes of the ALS pathophysiology, where metabolism is thought to be switched from sugars and carbohydrates to lipids use ( [33][34][35] ). To identify potential protein candidates for biomarkers analysis, we looked at highly regulated protein (unique peptides ≥ 2, LogFC < -0.693 or > 0.693, p-value < 0.05; 48 proteins in total) within the 69 pathways highlighted by FAT.…”
Section: Functional Analysismentioning
confidence: 99%
“…Microarray analysis and proteomics studies also provided evidence for a disturbed carbohydrate metabolism in ALS. Indeed, several studies explored the downregulation of glycolysis components in ALS patients, including the key enzymes phosphoglucomutase 2 like 1 and phosphoglycerate kinase [23,43]. Consistently, 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3) mRNA was found to be reduced in the post-mortem cortex of ALS patients [44].…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, both fALS and sporadic ALS (sALS) patients exhibit decreased weight and fat depots, which could be the result of a combined decrease in energy uptake, for example, due to a loss in appetite, and an increase in energy expenditure [17][18][19][20]. While dysbalanced energy homeostasis is an early event in ALS rodent models [21][22][23][24], it remains to be determined whether this is a primary or secondary event in ALS patients [4].…”
Section: Introductionmentioning
confidence: 99%